Analysis of Higher Order Thinking Skills (HOTS) in Reading Comprehension Question Final Test for Junior High School: Teachers' Voices - Zahro, Fatimatuz; Dzulfikri; Mistar, Junaidi; Sonny Elfiyanto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The purpose of this study is to investigate the strategies and approaches used to create HOTS questions in reading comprehension texts to improve students' HOTS skills. This study used a qualitative approach, relying on questionnaire data that results from teachers who created HOTS questions to explain and describe data. The subjects of this study were English teachers as participants. Researchers discovered numerous things using questionnaire data obtained via Google Forms. The research design is a case study, which describes teachers' perspectives on HOTS questions and the obstacles faced by teachers in creating HOTS questions. The research instrument was a questionnaire that was sent by Google Forms. In collecting data, the researcher sent the Google form link to the teacher and the researcher reviewed the answers from the teacher, and the data in this study were the teacher's answers to the questions about HOTS, which were attached to the Google form. The study's findings include three significant points 1. Teacher's challenges with drafting HOTS questions. 2. Teacher's strategies for using HOTS questions in reading comprehension question final test. 3. Teachers' technique or process for creating HOTS questions to increase students' HOTS skills. 4. How students respond to the teacher's queries. 5. The outcomes obtained by students using the HOTS method.